Assessing the demand and current status of agricultural mechanization in major coffee-production areas of Ethiopia - Tikuneh, Dessye Belay; Issa, Mubarek M; Tefera, Yared D (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2023)
Ethiopia, the primary coffee producer in Africa and the fifth in the world is facing challenges in agricultural mechanization. The research aims to assess the status, constraints, preferences, and demand of mechanization in Ethiopia, focusing on strategies to improve smallholder access to capital-intensive inputs and bridgethe gap between mechanization and farmers’ needs. A household survey and focus group discussions were conducted on 136 random samples using a multistage procedure, with semi-structured questionnaires used to interview 81 households of small-scale and 19 households of large-scale coffee farmers. The studyfound that preferences for each operation during coffee production are based on difficulties in work drudgery, with 42.45% believing that the first energy-consuming operation is hole digging for coffee plantation and cultivation. Coffee harvesting is a highly time-sensitive operation for 49.4% of smallholder farmers, with handtools being the main implement dominantly used for weeding. Poor harvesting practices reduce the quality of coffee during processing, and some unions have two or more wet mills using old machinery. The main challenges for low mechanization in Ethiopia include difficult topography, fragmented land, a lack of manpower,lack of awareness of technology, weak linkages of coffee mechanization channels, high technology costs, a shortage of running budgets, and a weak support system of cooperatives and unions. Experts suggest that capacity building on extension systems is the best way to facilitate the extension system of coffee mechanization technology. Assessments of technology manufacturers, machine assemblers, maintenance service providers, and importers were conducted in Harar, Hawassa, Jimma, Bonga, and Addis Ababa cities. Challenges include a lack of enabling laws and incentives to facilitate business start-ups. Importation of small-scale enginedriven equipment is an additional means to meet demand in some cooperativesand may provide farmers with an alternative source of cheaper machinery. Ethiopian academics and higher education institutions are essential players in exploring mechanization options, and public and private sectors, including cooperatives and farmer organizations, need to have a clear understanding of their respectiveresponsibilities and areas for collaboration.